Virulence of Five Isolates of The Entomopathogenic Fungus, Metarhizium anisopliae, Against Brown Planthopper (Nilaparvata lugens) - Trizelia Trizelia; Haliatur Rahma; My Syahrawati (Jurnal Proteksi Tanaman)
The brown planthopper (Nilaparvata lugens) is one of the main pests of rice plants. This pest attack can cause crop failure or puso. Biological control of this pest can be carried out using the entomopathogenic fungus, Metarhizium anisopliae. The ability of this fungus to control pests is influenced by the source of the isolate. The purpose of this study was to obtain isolates of M. anisopliae, which is virulent to N. lugens. This study used an experimental method with a completely randomized design (CRD) in six treatments and five replications. There were five isolates of M. anisopliae used and one control. M. anisopliae was applied to nymphs and adults of N. lugens with a concentration of 108 conidia/mL. The research revealed that all M. anisopliae isolates tested were virulent against N. lugens nymphs and adults. The most virulent isolate for the two stages of BPH was Met3B, which was collected from the leek rhizosphere. The isolate caused an adult mortality rate of 52%, nymph mortality of 60% in 10 days after application, and adults formed after application was only 37.33%.